2019
DOI: 10.1103/physrevd.100.074014
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the nonperturbative strong coupling from first principles

Abstract: The success of the screened massive expansion is investigated in the framework of a screened momentum-subtraction scheme for the running of the strong coupling in pure Yang-Mills theory. By the exact Slavnov-Taylor and Nielsen identities, a very predictive and self-contained set of stationary conditions are derived for the optimization of the fixed-coupling expansion, yielding explicit analytical one-loop expressions for the propagators, the coupling and the beta function, from first principles. An excellent a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 84 publications
(172 reference statements)
3
38
0
Order By: Relevance
“…. Some of them [12,14,22,26,29] fulfill the relation A(Q 2 ) = 0 at Q 2 = 0, i.e., the same relation that is fulfilled by the coupling A(Q 2 ) considered in this work. For reviews of a variety of holomorphic couplings, cf.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…. Some of them [12,14,22,26,29] fulfill the relation A(Q 2 ) = 0 at Q 2 = 0, i.e., the same relation that is fulfilled by the coupling A(Q 2 ) considered in this work. For reviews of a variety of holomorphic couplings, cf.…”
Section: Introductionsupporting
confidence: 56%
“…= 0.1989 is already above the maximum value achievable in our 3δ AQCD framework at that value of αs(M 2 Z ; MS). 29 We recall that the MM scheme is used in the large-volume lattice calculations of the Landau gauge gluon and ghost propagators [43,44], and the scheme is theoretically known at present up to the four-loop level [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, a very predictive analytical method has been developed [18][19][20][21] by a mere change of the expansion point of ordinary perturbation theory (PT) for the exact gauge-fixed Becchi-Rouet-Stora-Tyutin (BRST) invariant YM Lagrangian, yielding a screened massive expansion which is safe in the IR while recovering the correct results of ordinary PT in the UV. At oneloop and zero temperature, the screened expansion provides analytical results which are in excellent agreement with the lattice and can be easily continued to Minkowski space [21][22][23][24][25]. Thus the method provides a way to extract dynamical details like masses and damping rates from first principles.…”
Section: Introductionmentioning
confidence: 82%
“…Its renormalization in the Landau gauge was discussed in Refs. [56,57], where different renormalization schemes were considered and analytical expressions were reported for its beta function. The method has proven to be self-consistent and predictive when optimized by principles of gauge invariance [54,57].…”
Section: The Screened Massive Expansion Of Pure Yang-mills Theorymentioning
confidence: 99%
“…While in principle the failure of ordinary PT to describe the gluon's infrared mass could be attributed to its break down at low energies, in recent years a new approach to the perturbation theory of pure Yang-Mills (YM) theory has shown that most of the nonperturbative content of the gluon dynamic -at least as far as the two-point functions are concerned -can be absorbed into a shift of the expansion point of the Yang-Mills perturbative series. This approach, termed the screened massive expansion [47][48][49][50][51][52][53][54][55][56][57][58], is a simple extension of ordinary PT, formulated in such a way as to treat the transverse gluons as massive already at tree level while leaving the total action of the theory unchanged. The screened expansion has proven to be self-consistent to one loop -since it is renormalizable and leads to an infraredfinite and moderately small running coupling constant [57] -and predictive when optimized by principles of gauge invariance [54]; it yields two-point functions which are in excellent agreement with the lattice data in the Landau gauge [54,57].…”
Section: Introductionmentioning
confidence: 99%